Korean treatment recommendations for patients with axial spondyloarthritis - Mi Ryoung Seo; Jina Yeo; Jun Won Park; Yeon-Ah Lee; Ju Ho Lee; Eun Ha Kang; Seon Mi Ji; Seong-Ryul Kwon; Seong-Kyu Kim; Tae-Jong Kim; Tae-Hwan Kim; Hye Won Kim; et al. (The Korean Journal of Internal Medicine, 2023)
We aimed to develop evidence-based recommendations for treating axial spondylarthritis (axSpA) in Korea. The development committee was constructed, key clinical questions were determined, and the evidence was searched through online databases including MEDLINE, Embase, Cochrane, KoreaMed, and Kmbase. Systematic literature reviews were conducted, quality of evidence was determined, and draft recommendations were formulated according to the Grading of Recommendations Assessment, Development, and Evaluations methodology. Recommendations that reached 80% consensus among a voting panel were finalized. Three principles and 21 recommendations were determined. Recommendations 1 and 2 pertain to treatment strategies, regular disease status assessment, and rheumatologist-steered multidisciplinary management. Recommendations 3 and 4 strongly recommend patient education, exercise, and smoking cessation. Recommendations 5–12 address pharmacological treatment of active disease using nonsteroidal anti-inflammatory drugs, glucocorticoids, sulfasalazine, biologics, and Janus kinase inhibitors. Recommendations 13–16 address treatment in stable disease. We suggest against spa and acupuncture as therapies (Recommendation 17). Recommendations 18 and 19 pertain to total hip arthroplasty and spinal surgery. Monitoring of comorbidities and drug toxicities are recommended (Recommendations 20 and 21). Recommendations for axSpA treatment in a Korean context were developed based on comprehensive clinical questions and evidence. These are intended to guide best practice in the treatment of axSpA.